Deflation – Real Problem to be Solved or Inevitable Consequence of Globalization? - Mudra, Martin; Žamberský, Pavel; Villaverde, José; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The aim of this paper is to examine the striking inverse co-movement of decreasing inflation rates and increasing degree of globalization in developed economies during the current wave of globalization beginning in the 1980s. Our analysis stands on theoretical identification of channels through which globalization affects inflation in developed economies and the role of monetary policy in the process. Econometric estimation of the impact of advancing globalization on the rate of inflation carried out on a sample of high-income OECD countries over the years 1980 - 2013 supports our hypothesis that advancing globalization has a significant negative impact on the rate of inflation in advanced economies.
Vedoucí práce: Pavel Žamberský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses